Estudo da degradação de compostos nitroaromáticos utilizando fungos do gênero Pleurotus - Kist, Cristiane Patrícia (2013)
The fungi of the genus Pleurotus are basidiomycetes that stand out in the degradation of recalcitrant environmental substances. For example, nitroaromatic compounds, which are priority pollutants constituents of the effluent Red Water (RW), a wastewater generated in one of the manufacturing steps of commercial and military used explosive 2,4,6-trinitrotoluene (TNT). The objective of this work was to study the ability of fungi Pleurotus ostreatus and Pleurotus floridae POS 560 PSP 1 to degrade nitroaromatic compounds of the RW. The potential impact of this effluent was evaluated based on a relevant bibliographical history and through physical, chemical and ecotoxicological testing assessment. To evaluate aspects related to effluent ecotoxicology, bioassays were conducted using Daphnia magna, showing a toxicity factor (TF) 16 in a 1% RW concentration and FT 4 in a 0.5% RW concentration during a 24 hour testing, proving its toxicity and the importance of its treatment. The fungal treatability studies were based on the conduct of a procedure with factorial planning of experiments performed on solid medium, where growth was measured considering the variation of fungal species, pH, effluent concentration and glucose concentration. Among the most favorable factors, stood out the 0.5% effluent concentration, P. floridae fungus species, pH 6.0, and 10 g/L glucose concentration. These conditions were considered as the experimental basis for the fungal treatment of RW explosives industry effluent for 15 days in liquid medium in shaker flasks. The results indicated that P. floridae was able to reduce the parameters of COD, BOD and phenols at 55, 51 and 25% respectively. It was also obtained less toxicity compared to the bioassay using D. magna, where TF decreased to 4 in 48 hours. Additionally, P. floridae was able to fully convert and degrade both nitroaromatic compounds identified (2,4 and 2,6 dinitrotoluene) between 2 and 8 days interval. The results indicate and suggest that P. floridae have potential for the remediation of wastewater containing chemical species with environmental relevance as nitroaromatic compounds.